PENDIDIKAN DAN SISTEM PENDIDIKAN DI NEGARA INDONESIA DAN NEGARA LAIN - Abdul Wahab Syakrani; Abdul Hamid; Ahmad Bakri; M. Bahruddin; M. Khairun Najemi (ADIBA : JOURNAL OF EDUCATION, 2022)
The education system is a system consisting of components that exist in the educational process, where one component with other components is interconnected and interacts to achieve educational goals. The characteristics of education in Indonesia in the divine aspect have been developed in many ways, such as through religious education in schools and universities, through religious lectures in the community, through religious life in dormitories, through religious and divine pulpits. on television, via radio, newspapers and so on. The quality of education in Indonesia is getting worse. This is evident from the quality of teachers, learning facilities, and students. The causes of the low quality of education in Indonesia are the effectiveness of education in Indonesia, teaching efficiency in Indonesia and the standardization of education in Indonesia. To overcome the problems above, broadly speaking, there are two solutions that can be given, namely: First, a systemic solution, namely a solution by changing social systems related to the education system. Second, technical solutions, namely solutions that involve technical matters directly related to education.